2014
DOI: 10.1371/journal.pntd.0003140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Community-Based Lymphedema Management Program on Episodes of Adenolymphangitis (ADLA) and Lymphedema Progression - Odisha State, India

Abstract: BackgroundLymphedema management programs have been shown to decrease episodes of adenolymphangitis (ADLA), but the impact on lymphedema progression and of program compliance have not been thoroughly explored. Our objectives were to determine the rate of ADLA episodes and lymphedema progression over time for patients enrolled in a community-based lymphedema management program. We explored the association between program compliance and ADLA episodes as well as lymphedema progression.Methodology/Principal Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…Clinical diagnosis is accurate in settings where only podoconiosis is endemic; in settings where the two diseases may overlap, the combination of clinical history, physical examination, and blood tests for antifilarial antibody (Wb123 assay) have been used to reach a diagnosis. [33]…”
Section: Description Of Integrated Idm Ntd Implementationmentioning
confidence: 99%
“…Clinical diagnosis is accurate in settings where only podoconiosis is endemic; in settings where the two diseases may overlap, the combination of clinical history, physical examination, and blood tests for antifilarial antibody (Wb123 assay) have been used to reach a diagnosis. [33]…”
Section: Description Of Integrated Idm Ntd Implementationmentioning
confidence: 99%
“…At baseline, about 27% of patients had inter-digital entry lesions, 14% had advanced stage lymphedema (stages 4-6), and patients reported having lymphedema symptoms for an average of 25 years (data not shown). A previous paper concerning this cohort [16] provides more detail on demographic and LF disease characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Several papers have illustrated the effectiveness of lymphedema management programs in decreasing the frequency of ADL over time [12][13][14][15], Two studies evaluating the association between overall compliance and ADL found no association [6,12]. Another study found that among patients with inter-digital entry lesions, those who were compliant overall to a lymphedema management program had a lower rate of ADL episodes over time [16], but did not find this relationship among those without inter-digital entry lesions.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Community programs to promote leg hygiene have been successful at trivial cost. [13][14][15] An economic study of such a community program in Odisha, India estimated that the lifetime benefits of disability prevented, restored work capacity, and reduced medical expense would be 130 times the cost of the intervention. [16] In regions endemic with W. bancrofti, the most common manifestation of LF is hydrocele.…”
Section: Lymphatic Filariasis and Its Sequelaementioning
confidence: 99%